A privacy enhancing model for Internet of Things using three-way decisions and differential privacy. (May 2022) - Ali, Waqas; Nauman, Mohammad; Azam, Nouman
Abstract: The recent advancements in Internet of Things (IoT) have brought enormous advantages for businesses. These benefits are achieved by services that collect large volumes of data that is collected for analysis. The data may also contain sensitive information. Privacy of such data is an important research challenge. Differential privacy is a recent technique for data privacy. It works by anonymizing the attributes that may contain sensitive information. An essential step before applying differential privacy is the division of attribute set into three groups called sensitive, non-sensitive and ambiguous. A key issue in existing studies is that the division of attribute set is done manually by a domain expert and is therefore costly. We introduce a three-way approach for differential privacy and a supporting algorithm for this demarcation of attribute sets. Results indicate that the information content and stability of the dataset improves considerably with our approach. Graphical abstract: Highlights: Privacy is a major concern in data coming from the IoT devices. Attributes must be divided into three groups before applying differential privacy. Proposed approach divides the set of attributes into the three groups automatically. Proposed approach can be used to enhance the performance of differential privacy.